A collaboration framework to support decision making in new product development with the supply chain - Hasan, Syed; Shah, Satya; Gao, James X. (Cranfield University Press, 2013)
Management use the supply chain features more frequently, as the increasing rate of product introduc-tions demands more efforts from a business to deliver new products effectively and efficiently. To produce products at the targeted cost, time, and quality, the supply chain must be aligned with product development processes. This will allow manufacturing firms to overcome problems such as (partially) failed product launches due to the lack of timely provision of parts and systems caused by insufficient capacities in the supply chain. With integrated New Product Development (NPD) and Supply Chain Management (SCM), enterprises have the benefit of increased supply chain capability, thus increasing the effectiveness of new product introduction and improving their overall performance. In this re-search, the authors have tried to link NPD of an automotive manufacturer to its global network of suppliers. The integration points in the integrated NPD and SCM framework will provide guidelines to identifying where critical decision are made in collaboration with the supply chain.
Keywords: New product development; Collaboration; Decision making; Supply chain management